Малогабаритные бетатроны типа ПМБ - Ананьев Л. М. Лев Мартемьянович; Буров Г. И.; Кривчик В. Я.; Пеккер Я. С.; Отрубянников Ю. А.; Чахлов В. Л. Владимир Лукьянович; Шарашин Я. А.; Штейн М. М.; Ярушкин Ю. П. (1966, 1966)
В фонде НТБ ТПУ отсутствует